Law Enforcement Against Children As A Criminal Act Of Sexual Harassment (Case Study Of Decision Number 7/Pid.Sus-Anak/2020/Pn.Srg) - Cici Aputri; Hasuri Hasuri (Fakultas Hukum Universitas Sultan Ageng Tirtayasa, 2021)
Adolescence a child experiences the development of psychosexuality and emotionality that can affect a child's behavior. The developmental process experienced by adolescents can cause various kinds of problems for adolescents themselves from people who are close to their environment. Actions limited to juvenile delinquency that eventually lead to criminal acts require serious legal handling that provides protection of children's rights in the criminal justice process.Sexual abuse by children is a big problem that really needs special attention from the government. perpetrators of sexual harassment itself can occur in adults and children. The purpose of providing legal protection for perpetrators of criminal acts is to respect the rights of the perpetrators so that their fate is not hanging, there is legal certainty for perpetrators and to avoid arbitrary and unfair treatment. This study aims to determine the factors that cause the crime of sexual abuse among children in Cilegon City, to find out and to find out the judge's decision in law enforcement against children as perpetrators of sexual abuse among children in Cilegon City. The approach used in this study is a qualitative approach.